Justice-based ethics Challenging South African perspectives - Jones, Chris (AOSIS, 2018)
The book reflects academically on important and relevant ethical fields from a multidimensional South African context. The book challenges conventional borders from different ethical, theological, philosophical, economic and cultural perspectives with insight and expertise and seeks to add academic-ethical value, locally and globally, with its different points of departure deeply embedded in justice. From a mainly qualitative methodological perspective, this scholarly book demonstrates that ethics requires analytical thinking and critical people who, in an existentially and emancipatory way, can help make the world a more just, decent and humane place in which to live. The authors, who represent different academic and cultural backgrounds, present in their respective chapters their research systematically, intersectionally and constructivistically, based on profound theoretical analysis and reasoning. This epistemology results in an act of knowing that actively gives meaning and order to the reality to which it is responding. By doing this, they point out that people are in an ongoing process of becoming more human - allowing ourselves and our fellow human beings to flourish and to reach fuller potential through justice-based ethical reflection and action.